2005
DOI: 10.1159/000086782
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Carcinoma of the Breast

Abstract: We report an elderly case of an indolent breast tumor in a 66-year-old woman. The patient presented with a locally advanced mass in the right breast that was present for 13 years, accompanied by bleeding and ulceration since the last 5 years. She had a modified radical mastectomy with axillary dissection. She was found to have secretory carcinoma with a tumor size of 8 × 4 × 4 cm in diameter. Two out of the 22 removed lymph nodes were involved. The secretory material stained positive with lactalbumin, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…Tavassoli et al 4,5 reported that secretory carcinoma has been found in patients aged from 3 to 87 years of age (median 25 years). Ozguroglu et al 6 reported that most (approx. 70%) of the patients were over 20 years old and described the entity as a disease affecting adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tavassoli et al 4,5 reported that secretory carcinoma has been found in patients aged from 3 to 87 years of age (median 25 years). Ozguroglu et al 6 reported that most (approx. 70%) of the patients were over 20 years old and described the entity as a disease affecting adults.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8 Atypia is mild or moderate and mitotic activity is usually low. 3,6,7 A typical finding is the presence of secretory material both in the cytoplasm and in the glandular spaces formed by these cells. 7 These tumor cells contain PAS or α-lactalbumin-positive secretory material.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to the scarcity of reported cases, the significance of neoadjuvant chemotherapy, adjuvant chemotherapy, and postoperative radiotherapy remains unclear. Breast conservative surgery, modified radical mastectomy, and radical mastectomy are the most frequent procedures in adults, whereas simple mastectomy, local excision with sentinel lymph node biopsy, and complete axillary dissection are potentially adequate in children 26 . These were the surgical methods performed in our study patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that a papillary‐cystic growth pattern is characteristic in MASC, but a papillary‐predominant architecture has seldom been reported in breast SC. We have reviewed the previous studies of SC from 1980 to 2015; SC with a focal papillary pattern or an intraductal papillary component was described in a few studies (Table ) . Only two cases of SC with a predominantly papillary growth pattern were reported, and the significance of this uncommon morphological feature was not discussed further.…”
Section: Discussionmentioning
confidence: 99%